2013
DOI: 10.4161/cbt.22628
|View full text |Cite
|
Sign up to set email alerts
|

Small molecule kinase inhibitors block the ZAK-dependent inflammatory effects of doxorubicin

Abstract: The adverse side effects of doxorubicin, including cardiotoxicity and cancer treatment-related fatigue, have been associated with inflammatory cytokines, many of which are regulated by mitogen-activated protein kinases (MAPKs). ZAK is an upstream kinase of the MAPK cascade. Using mouse primary macrophages cultured from ZAK-deficient mice, we demonstrated that ZAK is required for the activation of JNK and p38 MAPK by doxorubicin. Nilotinib, ponatinib and sorafenib strongly suppressed doxorubicin-mediated phosph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
56
0
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 61 publications
(65 citation statements)
references
References 42 publications
7
56
0
2
Order By: Relevance
“…Sorafenib 46 inhibits vascular endothelial growth factor receptor and platelet-derived growth factor receptor and is clinically used to treat renal cell carcinoma, hepatocellular carcinoma, and thyroid carcinoma. We have previously shown that all three of these tyrosine kinase inhibitors block the expression of inflammatory genes by BMDM following exposed to doxorubicin 34 . In the presence of these inhibitors, the expression of RNA encoding IL-1β, IL-6, and CXCL-1 by doxorubicin, vincristine, or both was blocked (Fig.…”
Section: Resultsmentioning
confidence: 78%
See 1 more Smart Citation
“…Sorafenib 46 inhibits vascular endothelial growth factor receptor and platelet-derived growth factor receptor and is clinically used to treat renal cell carcinoma, hepatocellular carcinoma, and thyroid carcinoma. We have previously shown that all three of these tyrosine kinase inhibitors block the expression of inflammatory genes by BMDM following exposed to doxorubicin 34 . In the presence of these inhibitors, the expression of RNA encoding IL-1β, IL-6, and CXCL-1 by doxorubicin, vincristine, or both was blocked (Fig.…”
Section: Resultsmentioning
confidence: 78%
“…Bacterial pore-forming toxins, bacterial and viral pathogens, asbestos, silica, ATP, double-stranded RNA, uric acid crystals, and translation inhibitors (such as emetine and ribotoxic stressors including doxorubicin) stimulate IL-1β processing via the NLRP3-inflammasome. Of cancer chemotherapeutic agents, gemcitabin and 5-FU have been shown to activate the inflammasome in myeloid-derived suppressor cells; 40 doxorubicin has been shown to do the same in macrophages 34 , 41 …”
Section: Introductionmentioning
confidence: 99%
“…ZAK is critically important for JNK activation upstream of MKK4 and MKK7(28) and is important for doxorubicin-induced apoptosis(29, 30). TAOK2 has been implicated to be an activator of JNK as well(3135).…”
Section: Resultsmentioning
confidence: 99%
“…Evidences are accumulating regarding a potential anti-inflammatory effect of nilotinib in different experimental models [19,24,47]. Herein, nilotinib's ability to reduce oxidative stress, boost host antioxidant defense mechanism and immune system, and reduce expression Fig.…”
Section: Discussionmentioning
confidence: 96%